Neuronal ERK signaling in response to graphene oxide in nematode Caenorhabditis elegans. Issue 4 (21st April 2017) - Qu, Man; Li, Yunhui; Wu, Qiuli; Xia, Yankai; Wang, Dayong
Abstract: ERK signaling is one of the important mitogen-activated protein kinases (MAPKs). However, the role of ERK signaling in the regulation of response to engineered nanomaterial exposure is still largely unclear. In this study, using in vivo assay system of Caenorhabditis elegans, we investigated the function of ERK signaling in response to graphene oxide (GO) exposure and the underlying molecular mechanism. GO exposure increased the expression of MEK-2/MEK and MPK-1/ERK in the ERK signaling pathway. Mutation of mek-2 or mpk-1 resulted in a susceptibility to GO toxicity. Both the MEK-2 and the MPK-1 acted in neurons to regulate the response to GO exposure, and the neuronal expression of MEK-2 or MPK-1 caused a resistance to GO toxicity. In the neurons, SKN-1b/Nrf acted downstream of the MPK-1, and AEX-3, a guanine exchange factor for GTPase, further acted downstream of the SKN-1b to regulate the response to GO exposure. Therefore, a signaling cascade of MEK-2-MPK-1-SKN-1b/-AEX-3 was identified in the neurons required for the regulation of response to GO exposure. Moreover, genetic interaction assay demonstrated that the neuronal ERK signaling-mediated signaling pathway and the intestinal p38 MAPK-mediated signaling pathway functioned synergistically in the regulation of response to GO exposure. Our results highlight the crucial function of the neuronal ERK signaling in the regulation of response to nanomaterial exposure in organisms.